Urgency of Strengthening Women Participation in The Building of Gender Justice Based Village - Sapto Budoyo; Marzellina Hardiyanti (LAW REFORM, 2021)
Village building is part of national building which is regulated in Law No. 6 Year 2014 on Village. People participation is necessary in the building of villages, including the participation of women which is still considered very low particularly in generating their aspiration to build villages. Therefore, strengthening women participation in village building is necessary so that policies regarding women issues can be well accommodated in order to realize village building which is based on gender justice. Law research method was appllied in this study using literature approach in order to collect accurate data. The result of this study shows that it is necessary to strengthen women participation in village building which is based on gender justice because it is indicated that political law in Indonesia tends to support the issue corcerning legal protection toward women position as citizens. This is regulated in constitutional foundation in   Article 27 section (1), Article 28D section (1), and Article 28I section (2) The 1945 Constitution of The Republic of Indonesia and Article 55 No.6 Year 2014 Law on Village. Women representation in villages aims to solve various issues related to women justice particularly on issues around violence cases which seems like a tip of an iceberg and are unresolved. The efforts to strengthen women participation in village building are built through the form of togetherness, growing from root, trust and openness.